Analisis de secuencias de genes de Coffea Arabica var.caturra - Montoya O, G.E.=700 1 Cristancho A, M.A.; Moncada B, M. del P.
(Es, En)
ilus., 20 ref.
Keywords: COFFEA ARABICA; RESERVAS GENETICAS; ADN; COLOMBIA; FUNCION PROTEICA PUTATIVA